(3QSGdI aj GdehGYXs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3CMeO Hf eMjj GdOjfs)
(3ChdgG (B:s
(3GdMeO ddg hMOg hdG jOhe EdG edcg, hGdUdGI hGdSdGe Ydi ef dG fHj HYOghHYOCjgG GdGHf GdeHGQc Sdc Gddg Hj hHc CMSf GdefGgL hGdeSGdc Efc SCdJfj YeG hLOfG Ydjg BHGAfG ef Cf GdGHf dG jLJeY ef CHjg Ch UgQg hef aj eYfGge cTjNg eY hLhO hdOgs
(3BNQgG (B:s
(3bGd HYV GdYGQajf ef de jcf dg ef gPG GdYde TjA CNTi Ydjg ShA GdNGJeI hCOfi GdfUjH efg (B() (3Hg hGdJSdje dCgdg hGddg SHMGfg hJYGdi CYdes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3aj Chdg Jedc HGSe YHO Gddg OgJhjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs